Mercury anomalies across the Palaeocene–Eocene thermal maximum - Jones, M; Percival, L; Stokke, E; Frieling, J; Mather, T; Riber, L; Schubert, B; Schultz, B; Tegner, C; Planke, S; Svensen, H (European Geosciences Union, 2019)
Large-scale magmatic events like the emplacement of the North Atlantic Igneous Province (NAIP) are often coincident with periods of extreme climate change such as the Palaeocene–Eocene Thermal Maximum (PETM). One proxy for volcanism in the geological record that is receiving increased attention is the use of mercury (Hg) anomalies. Volcanic eruptions are among the dominant natural sources of Hg to the environment; thus, elevated Hg∕TOC values in the sedimentary rock record may reflect an increase in volcanic activity at the time of deposition. Here we focus on five continental shelf sections located around the NAIP in the Palaeogene. We measured Hg concentrations, total organic carbon (TOC) contents, and δ13C values to assess how Hg deposition fluctuated across the PETM carbon isotope excursion (CIE). We find a huge variation in Hg anomalies between sites. The Grane field in the North Sea, the most proximal locality to the NAIP analysed, shows Hg concentrations up to 90 100 ppb (Hg∕TOC = 95 700 ppb wt %−1) in the early Eocene. Significant Hg∕TOC anomalies are also present in Danish (up to 324 ppb wt %−1) and Svalbard (up to 257 ppb wt %−1) sections prior to the onset of the PETM and during the recovery period, while the Svalbard section also shows a continuous Hg∕TOC anomaly during the body of the CIE. The combination with other tracers of volcanism, such as tephra layers and unradiogenic Os isotopes, at these localities suggests that the Hg∕TOC anomalies reflect pulses of magmatic activity. In contrast, we do not observe clear Hg anomalies on the New Jersey shelf (Bass River) or the Arctic Ocean (Lomonosov Ridge). This large spatial variance could be due to more regional Hg deposition. One possibility is that phreatomagmatic eruptions and hydrothermal vent complexes formed during the emplacement of sills led to submarine Hg release, which is observed to result in limited distribution in the modern era. The Hg∕TOC anomalies in strata deposited prior to the CIE may suggest that magmatism linked to the emplacement of the NAIP contributed to the initiation of the PETM. However, evidence for considerable volcanism in the form of numerous tephra layers and Hg∕TOC anomalies post-PETM indicates a complicated relationship between LIP volcanism and climate. Factors such as climate system feedbacks, changes to the NAIP emplacement style, and/or varying magma production rates may be key to both the onset and cessation of hyperthermal conditions during the PETM. However, processes such as diagenesis and organic matter sourcing can have a marked impact on Hg∕TOC ratios and need to be better constrained before the relationship between Hg anomalies and volcanic activity can be considered irrefutable.